Structures Formation on the Y-TZP-AI[2]O[3] Ceramic Composites Surface - Kulkov S. N. Sergey Nikolaevich; Sevostyanova I. Irina; Sablina T. Tatiana; Buyakova S. P. Svetlana Petrovna; Pshenichnyy A. Artem; Savchenko N. Nickolai (2016, 2016)
Title screen